UPAYA DAN BUDAYA PERLINDUNGAN PEREMPUAN TERHADAP HONOR KILLING DI MASYARAKAT PAKISTAN DALAM HUKUM INTERNASIONAL: Efforts and Cultural Frameworks for the Protection of Women from Honor Killings in Pakistani Society under International Law - Angel June Anabelle; Ayu Nrangwesti (Faculty of Law, Universitas Trisakti, 2025)
Honor killing is a form of gender-based violence that persists in Pakistan, where women are murdered by family members for allegedly dishonoring the family. Although the Pakistan Penal Code has been amended to criminalize this practice, its enforcement remains weak due to patriarchal culture, tribal influence, and legal loopholes in the qisas and diyat mechanisms that allow impunity for perpetrators. The problem formulation in this study aims to examine the extent to which Pakistan’s legal framework on honor killings aligns with international human rights principles, particularly the ICCPR and CEDAW. The research adopts a normative juridical method with a legal synchronization approach, using literature review and qualitative analysis of domestic laws and international instruments. The result of this study indicate that despite legislative efforts, protection for women remains ineffective due to weak law enforcement, underreporting, and the dominance of customary norms. This situation violates the state’s obligation to guarantee the right to life and the principle of non-discrimination. The study concludes that comprehensive legal reform, stronger enforcement, and transformative social change are urgently needed to eliminate honor killings and to ensure genuine protection of women’s rights.